Service-Learning and Disability Simulations: Comparing Their Influence on Candidate Teaching Dispositions - Schreiner, Mary B (International Journal of Research on Service-Learning in Teacher Education, 2016)
As one of five key standards for program accreditation, the Council for the Accreditation of Educator Preparation expects graduates to display dispositions necessary to demonstrate positive impact on all P-12 students learning and development (2015). In this study, service-learning experiences and disability simulations were explored as two teaching tools within a required introduction to disabilities course, to see if either would promote certain teaching dispositions toward the candidates future students with disabilities. Two specific dispositions that showed measurable change in candidate levels were the dispositions of empathizing and advocating. Results of this study suggest that both service-learning and simulations are viable options for teacher educators who wish to address teaching dispositions in early courses about disability.